Processing PDF Documents Written in Macedonian Language Using UiPath Document Understanding - Krpachovska, Marija; Mirceva, Georgina (Ss Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2023)
Given the rapid advancement of technology over the past decades, the digitalization of repetitive processes is inevitable and for most parts of the world, it is already a reality. With the possibilities to make the execution of everyday tasks quicker, more precise, less expensive, and overall more efficient, it is not surprising that so many companies and institutions have already started transforming their processes to take full advantage of the benefits that current technology has to offer. Despite all this, when it comes to process automation in Macedonia there are still many areas in which there is room for further development. The purpose of this paper is to explore the possibilities, as well as the limitations that current technology has to offer in regard to processing PDF documents written in Macedonian language, more specifically focusing on Hipbath Document Understanding.
Keywords: UiPath, RPA, PDF, automation, digitalization, document understanding, business process, workflow, package, JSON